Seasonal variation in glucose and insulin is modulated by food and temperature conditions in a hibernating primate - Blanco, Marina B.; Greene, Lydia K.; Ellsaesser, Laura N.; Williams, Cathy V.; Ostrowski, Catherine A.; Davison, Megan M.; Welser, Kay; Klopfer, Peter H. (Frontiers in Physiology, 2023)
Feast-fast cycles allow animals to live in seasonal environments by promoting fat storage when food is plentiful and lipolysis when food is scarce. Fat-storing hibernators have mastered this cycle over a circannual schedule, by undergoing extreme fattening to stockpile fuel for the ensuing hibernation season. Insulin is intrinsic to carbohydrate and lipid metabolism and is central to regulating feast-fast cycles in mammalian hibernators. Here, we examine glucose and insulin dynamics across the feast-fast cycle in fat-tailed dwarf lemurs, the only obligate hibernator among primates. Unlike cold-adapted hibernators, dwarf lemurs inhabit tropical forests in Madagascar and hibernate under various temperature conditions. Using the captive colony at the Duke Lemur Center, we determined fasting glucose and insulin, and glucose tolerance, in dwarf lemurs across seasons. During the lean season, we maintained dwarf lemurs under stable warm, stable cold, or fluctuating ambient temperatures that variably included food provisioning or deprivation. Overall, we find that dwarf lemurs can show signatures of reversible, lean-season insulin resistance. During the fattening season prior to hibernation, dwarf lemurs had low glucose, insulin, and HOMA-IR despite consuming high-sugar diets. In the active season after hibernation, glucose, insulin, HOMA-IR, and glucose tolerance all increased, highlighting the metabolic processes at play during periods of weight gain versus weight loss. During the lean season, glucose remained low, but insulin and HOMA-IR increased, particularly in animals kept under warm conditions with daily food. Moreover, these lemurs had the greatest glucose intolerance in our study and had average HOMA-IR values consistent with insulin resistance (5.49), while those without food under cold (1.95) or fluctuating (1.17) temperatures did not. Remarkably low insulin in dwarf lemurs under fluctuating temperatures raises new questions about lipid metabolism when animals can passively warm and cool rather than undergo sporadic arousals. Our results underscore that seasonal changes in insulin and glucose tolerance are likely hallmarks of hibernating mammals. Because dwarf lemurs can hibernate under a range of conditions in captivity, they are an emerging model for primate metabolic flexibility with implications for human health.